COMPARISON OF HOLISTIC CARE HYPNOLACTATION MODEL BY SELF-TALK FOR BREASTMILK PRODUCTION IN POSTPARTUM WOMEN - Ningrum, Mudy Okti; ,, Risnawati; Maharani, Kristina (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2024)
Breast milk production is crucial for mothers to provide exclusive breast milk to their babies. Holistic care in midwifery offers an alternative or complementary approach to conventional medical treatment. It aimed to enhance the health of postpartum mothers through education and various health services, recognizing that health issues are not solely physical and can be addressed through non-medical interventions. This study investigated the impact of Hypnolactation and self-talk on breast milk production in postpartum mothers. The research utilized a quasi-experimental design, specifically, a pretest-posttest with a control group. The holistic care model implemented communication science techniques to promote relaxation, deep breathing, positive suggestions, and confidence building in postpartum mothers. The study was conducted in the Meteseh Boja Kendal village area from June to August 2023. The analysis employed paired testing, with a sample of 35 out of 42 postpartum mothers selected through purposive sampling. The results revealed that 100% of mothers who received Hypnolactation achieved sufficient breast milk levels, whereas 66.7% of those who practiced self-talk achieved the same, with 33.3% having inadequate levels. Hypnolactation demonstrated greater efficacy in enhancing breast milk production in the Meteseh Boja Kendal area. Applying hypnolactation and self-talk increased the secretion of endorphins, prolactin, and oxytocin, potentially influencing the mother's breastfeeding ability and the body's capacity to produce breast milk. Future research should consider using action research methods, expanding sample coverage over an extended period, and examining additional factors such as postpartum mothers' dietary intake.